2002
DOI: 10.1002/pen.11018
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic behavior of nylon 6/saponite and nylon 6/montmorillonite nanocomposites

Abstract: X-ray diffraction methods and DSC thermal analysis have been used to investigate the structural change of nylon 6/clay nanocomposites. Nylon 6/clay has prepared by the intercalation of s-caprolactam and then exfoliaton of the layered saponite or montmorillonite by subsequent polymerization. Both X-ray diffraction data and DSC results indicate the presence of polymorphism in nylon 6 and in nylon 6/clay nanocomposites. This polymorphic behavior is dependent on the cooling rate of nylon 6/clay nanocomposites from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 25 publications
(4 reference statements)
2
59
0
Order By: Relevance
“…Adding nanoclay to the blend led to a small increase in crystallization temperature as compared to the PA6/FR/elastomer blend. This may be because of the well-known nucleation effect for PA6/clay nanocomposites [25,26].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Adding nanoclay to the blend led to a small increase in crystallization temperature as compared to the PA6/FR/elastomer blend. This may be because of the well-known nucleation effect for PA6/clay nanocomposites [25,26].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In the case of Nylon6/synthetic saponite nanocomposites, Wu et al have noted that the addition of synthetic saponite increased the crystallization rate of the α -form at a lower saponite content and promoted a heterophase nucleation of the γ -phase at a higher synthetic saponite content [98,108] . Phang et al reported that only the α -form crystalline structure was formed upon incorporating MWCNTs into PA6 matrix, and the cooling rate and annealing conditions did not affect the crystal form [109] .…”
Section: Polymorphism In Nylonmentioning
confidence: 99%
“…Among the different types of clay, montmorillonite, hectorite and saponite 3,13,15,16 are most commonly used as rubber fillers. Bentonite is barely used as the rubber filler with only a few reports.…”
Section: Introductionmentioning
confidence: 99%